KARATERISTIK HABITAT MUSIM DINGIN SIKEP MADU ASIA (PERNIS PTYLORHYNCHUS) DI TALAGA BODAS, JAWA BARAT BERBASIS DATA SATELLITE TRACKING - Presti Ameliawati; . Syartinilia; Yeni A. Mulyani; Hiroyoshi Higuchi (Jurnal Lanskap Indonesia, 2013)
ABSTRACTOriental Honey Buzzards (OHBs, Pernis ptilorhynchus) are migratory raptors which have wintering grounds in Indonesia. OHBs’ wintering habitats can be divided into core and edge habitats with unique landscape characteristics, which influence wintering site selection.TalagaBodasandsurroundingareahas beenidentifiedas wintering habitat of OHB based satellite tracking data. Theobjective of this study were to: 1) modeling the distribution of wintering habitat of OHB in Talaga Bodas; 2) analyzemicro habitats of vegetationaspect inTalagaBodas; 3) implications of wintering habitatmanagement inWest Java. Main methodology was combining satellite-tracking data of OHB with the GIS/remote sensing datausing logistic regression model. 18 Environmental variable used in this study include nearest distance to the elevation (0-300m, 300-500m, 500-700m, 700-1000m, >1000m),slope (0-3%, 3-8%, 8-15%, 15-25%, 25-40%, >40%) and landcover (water body, paddy field,abandon land,settlement,shrub,plantation,forest). Only 7 variables were detected as important variable for characteririzing the distribution of wintering habitat. Wintering habitat distribution model werepredominantly influenced by 1) slope 25%-40%, 2) elevation 0-300 m, 3) elevation 300-500 m, 4) elevation >1000 m, 5) forest, 6) paddy field and 7) water body. The results of the vegetation analysis’s known that the core habitat biodiversity tend to have less variable than the edge habitats.The results ofthis studywillbe usedformanagement ofwinteringhabitat for OHB.Key words:logistic regression, oriental honey-buzzards, satellite tracking, talaga bodas, wintering habitat